Novel synthetic chalcone‐coumarin hybrid for Aβ aggregation reduction, antioxidation, and neuroprotection. (14th September 2018) - Lee, Shin‐Ying; Chiu, Ya‐Jen; Yang, Shu‐Mei; Chen, Chiung‐Mei; Huang, Chin‐Chang; Lee‐Chen, Guey‐Jen; Lin, Wenwei; Chang, Kuo‐Hsuan
Abstract: Background: Aggregation of misfolded amyloid β (Aβ) in senile plaques causes oxidative stress and neuronal death in Alzheimer's disease (AD). Compounds possessing antiaggregation and antioxidant properties are promising candidate compounds for AD treatment. Methods: We examined the potential of synthetic derivatives of licochalcone A and coumarin for inhibiting Aβ aggregation, scavenging reactive oxygen species (ROS), and providing neuroprotection by using biochemical assays and Tet‐On Aβ‐GFP 293/SH‐SY5Y cell models for AD. Results: Among test compounds, LM‐031, a novel chalcone‐coumarin hybrid, inhibited Aβ aggregation and scavenged free oxygen radicals. LM‐031 markedly reduced Aβ misfolding and ROS as well as promoted neurite outgrowth and inhibited acetylcholinesterase in Tet‐On Aβ‐GFP 293/SH‐SY5Y cells. Mechanistic studies showed upregulation of the HSPB1 chaperone, NRF2/NQO1/GCLC pathway, and CREB/BDNF/BCL2 pathway. Decreased neurite outgrowth upon the induction of Aβ‐GFP was rescued by LM‐031, which was counteracted by knockdown of HSPB1, NRF2, or CREB. Conclusion: Taken together, these findings demonstrate that LM‐031 exhibited antiaggregation, antioxidant, and neuroprotective effects against Aβ toxicity by enhancing HSPB1 and the NRF2‐related antioxidant pathway as well as by activating the CREB‐dependent survival and antiapoptosis pathway. These results imply that LM‐031 may be a new therapeutic compound for AD.